Sustainable entrepreneurship practices and performance among Malaysian herbal-based SMEs - Auwal, Abdullahi Muhammad (2018)
Entrepreneurial activities have contributed greatly to environmental pollution. Such pollution has caused a disastrous effect on us and has also been transferred to our future generations. In the light of this, sustainable entrepreneurship practice (SEP) has been promoted as a resolution of environmental problems capable of addressing environmental pollution, climate change issues, public health, and safety concerns, diverse consumption patterns, and has become critical for competing in international markets. Recently, the Malaysian government has made a strong commitment to strengthening sustainability stressing on the importance of implementing SEP to address environmentally friendly issues. Despite this, the level of herbal-based SMEs involvement is still low because of low awareness and knowledge of its importance among the herbal-based SMEs and consumers in Malaysia. Therefore, there is need to determine the SEP implementation level of the Malaysian herbal-based SMEs and how it benefits them in controlling activities that may adversely affect the environment at various stages of manufacturing, distribution and retailing sub-sectors. Literature shows that sustainability drivers; external pressure (EP) and top leadership culture (TLC) provide the impetus for small and medium-sized enterprises (SMEs) to achieve competitive advantage and thus compete successfully in the marketplace. This study intends to investigate the standpoints of herbal-based small and medium-sized enterprises (SMEs) with emphasis on level of SEP implementation towards achieving sustainability performance within business dynamics in Malaysia. The study explores the effectiveness of EP, TLC and strategic sustainability orientation (SSO) on the SEP implementation towards performance among the respondents. 300 herbal-based SMEs were surveyed using structured questionnaire. The respondents were asked questions on SEP awareness, current SEP implementation level, sustainability performance, and lastly their firm profile. Items were measured using 5- point Likert Scale statements, and data collected were analyzed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and Structural Equation Model (SEM). The empirical findings showed that SEP implementation has an impact on sustainability performance (economic, environmental and social) among the Malaysian herbal-based SMEs. Besides, the findings again provide a better understanding on how the herbal-based SMEs formulated SSO as a business strategy, and how the SSO mediated the relationship between EP, TLC, and SEP implementation to effectively create favorable sustainability performance, accounting for 62 percent variance. The result also indicated that higher level of SEP implementation was positively related to sustainability performance (economic, environmental and social) among the respondents in the industry, accounting for 47 percent variance. Moreover, the moderation effect results revealed that both general awareness on SEP and Good Management Practice (GMP) certification moderated most of the exogenous construct paths. In sum, the findings contribute to Triple-Bottom-Line (TBL) literature based on the incorporation of Institutional Theory (IT), Strategic Choice Theory (SCT), Strategic Orientation Theory (SOT), and Resource-Based View Theory (RBV) in entrepreneurship sustainability framework, as such framework is lacking within Malaysian herbal industry. In terms of practical implications, the findings will serve as a relevant benchmark for sustainability, that is, how SMEs generate a sustainable competitive advantage in Malaysia. In conclusion, this research suggests that the government (through agencies like DOA, FRIM, MARDI, and NPRA) should come up with dedicated policies and programs on the importance of forming SSO towards implementing SEP through enlightenment campaigns, showcasing its influence on business strategy formulation and performance enhancement.